Fe(III) (oxyhydr)oxide reduction by the thermophilic iron-reducing bacterium Desulfovulcanus ferrireducens - Sklute, Elizabeth C.; Leopo, Deborah A.; Neat, Kaylee A.; Livi, Kenneth J. T.; Dyar, M. Darby; Holden, James F. (Frontiers in Microbiology, 2023)
Some thermophilic bacteria from deep-sea hydrothermal vents grow by dissimilatory iron reduction but our understanding of their biogenic mineral transformations is nascent. Mineral transformations catalyzed by the thermophilic iron-reducing bacterium Desulfovulcanus ferrireducens during growth at 55°C were examined using synthetic nanophase ferrihydrite, akaganéite, and lepidocrocite separately as terminal electron acceptors. Spectral analyses using visible-near infrared (VNIR), Fourier-transform infrared attenuated total reflectance (FTIR-ATR), and Mössbauer spectroscopies were complemented with X-ray diffraction (XRD) and transmission electron microscopy (TEM) using selected area electron diffraction (SAED) and energy dispersive Xray (EDX) analyses. The most extensive biogenic mineral transformation occurred with ferrihydrite, which produced a magnetic, visibly dark mineral with spectral features matching cation deficient magnetite. D. ferrireducens also grew on akaganéite and lepidocrocite and produced non-magnetic, visibly dark minerals that were poorly soluble in oxalate solution. Bioreduced mineral products from akaganéite and lepidocrocite reduction were almost entirely absorbing in the VNIR in contrast to both parent minerals and the abiotic controls. However, FTIR-ATR and Mössbauer spectra and XRD analyses of both biogenic minerals were almost identical to the parent minerals and the controls. TEM of these biogenic minerals showed the presence of poorly crystalline iron nanospheres (50-200 nm diameter) of unknown mineralogy that were likely coating the larger parent minerals and were absent from the controls. The study demonstrated that thermophilic bacteria transform different types of Fe(III) (oxyhydr)oxide minerals for growth with varying mineral products. These mineral products are likely formed through dissolution-reprecipitation reactions but are not easily predictable through chemical equilibrium reactions alone.